2021
DOI: 10.1148/radiol.2021210490
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Allergic-like Reactions at Repeat CT: Steroid Pretreatment versus Contrast Material Substitution

Abstract: Background: It is unclear whether steroid premedication is an effective means of preventing repeat allergic-like reactions in high-risk patients with a previous allergic-like reaction to iodinated contrast material (ICM).Purpose: To compare the effectiveness of ICM substitution (ie, using iohexol in a patient with a previous iopromide reaction) with 12-and 2-hour steroid premedication for preventing repeat acute allergic-like reactions in high-risk patients. Materials and Methods:This retrospective study ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…About 10% of people still experience a breakthrough reaction while taking steroids, especially if the previous reaction was severe ( Davenport et al, 2009 ). Recent research suggests that switching to a non-allergenic contrast media is more effective in reducing subsequent reactions than steroid premedication ( Schrijvers et al, 2019 ; McDonald and Larson, 2021 ). However, ICM use is unavoidable in many disease evaluations, so for high-risk patients, we preferred to change the type of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of people still experience a breakthrough reaction while taking steroids, especially if the previous reaction was severe ( Davenport et al, 2009 ). Recent research suggests that switching to a non-allergenic contrast media is more effective in reducing subsequent reactions than steroid premedication ( Schrijvers et al, 2019 ; McDonald and Larson, 2021 ). However, ICM use is unavoidable in many disease evaluations, so for high-risk patients, we preferred to change the type of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had several limitations. Firstly, this review did not include one article [ 43 ] in the results section because this analysis was completed and submitted before the article was published. It was a single-center, retrospective study conducted in America.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with a history of reaction to contrast, premedication is another strategy to reduce the risk of reaction in situations when contrast is required. The use of premedication is controversial [ 20 , 22 , 28 , 40 , 44 , 48 , 52 , 77 , 78 , 81 84 ]. Studies have shown that premedication is useful in reducing the incidence of, but not preventing, immediate and non-immediate reactions to contrast [ 22 , 52 , 80 , 85 87 ].…”
Section: Contrast Hypersensitivity Preventionmentioning
confidence: 99%